Pengaruh Online Customer Review Terhadap Keputusan Pembelian Dengan Harga Sebagai Variabel Intervening Di Market Place Shopee (Studi Pada Mahasiswa FEB Angkatan 2019 Universitas Muhammadiyah Metro) - Intan Ayu Delisa; Ardiansyah Japlani; Iqbal Mei Setiawan (Jurnal Manajemen DIVERSIFIKASI, 2025)
Internet users have gone a step further not only to communicate but also to book vehicles,trade, work and even buy property. With the emergence of consumers' need to make decisionsquickly without being bound by space and time as well as the need to manifest themselves incyberspace, this will have a direct or indirect impact on consumer behavior in buying andusing products online. The survey method was chosen as the primary data source. The surveymethod focuses on collecting data from respondents who have certain information, thusenabling researchers to solve problems. Data collection was carried out using aquestionnaire instrument or questionnaire. In this study, the population was undergraduatestudents at UM Metro, namely students at the Faculty of Economics. The sampling techniqueused accidental sampling with a total sample of 75 people. Data collection techniques usinga questionnaire with a Likert scale. The results of the study show that 1) there is a positiveand significant influence between Online Customer Reviews on Purchasing Decisions 2)there is a positive and significant influence between Online Customer Reviews on Price 3)there is a positive and significant influence between Price on Purchase Decision